Empowering the Future: A Study on the Deep Integration Path of Social Educational Resources and Family Education (Journal of educational development exploration, 2026)
Amid the ongoing transformation toward educational modernization, the systematic integration of family education with social educational resources has become a central issue for transcending traditional educational boundaries and enhancing adolescents’ core competencies. Grounded in Bourdieu’s theory of cultural capital and constructivist learning theory, this study systematically analyzes the educational value dimensions of core social educational resources such as museums, science centers, public libraries, and cultural venues. Drawing on parent-child education practices in Beijing, Shanghai, and other localities, it illustrates their empirical effects in cultivating humanistic literacy, shaping scientific thinking, and improving self-directed learning abilities. From the perspectives of educational continuity construction, interaction depth enhancement, and learning-outcome transformation mechanisms, the paper constructs a “pre-planning—process guidance—post-transformation” parent-child practice model. To address real-world barriers such as information asymmetry, time conflicts, and lack of professional guidance, it proposes a three-dimensional solution featuring platform-based integration, mechanized innovation, and professional empowerment. This research aims to provide parents with an action framework that combines theoretical support and practical guidance, offering academic reference for promoting the high-quality development of family education.
Keywords: Family education; Social educational resources; Parent-child practice; Core competencies; Cultural capital; Constructivism; Educational integration; Practical pathways